Exploring students’ climate change perception: the key factor of climate change mitigation and adaptation - Maisuna Kundariati; I. Ibrohim; Fatchur Rohman; Safwatun Nida; Wachidah Hayuana; Zia Aulia Zaidin Putra (JPBI (Jurnal Pendidikan Biologi Indonesia), 2024)
Climate change has felt by all individual now. Its impact is massive change in human daily life across countries. Therefore, it is necessary to assess students, as a youth, climate change perception. This study aimed to analyze the tenth grader students’ climate change perception. This study is a quantitative design, with survey method. Using questioners, we were collected 283 high school students in Malang, Indonesia. All students are willing to giving their answer to the questions. Students were asked to rate the items based on the quality and relevance to the type of climate change perception that these items were supposed to assess on a scale from 1 (Terrible) to 5 (Excellent). The five items for each type of climate change perception were selected with 25 item questions in total. Five categories are: 1) reality (Q1-Q5), 2) causes (Q6-Q10), 3) valence of consequences (Q11-Q15), 4) spatial distances (Q16-Q20), 5) temporal distances (Q21-Q25). This study reveals that students have a belief that climate change is real. Some students have used to doing good habits to reduce energy use and have the will to tackle the crisis. Students also believe that climate change was caused by the human activities rather than natural phenomenon. Students have a good understanding of climate change, but there are still many students who have not yet taken their action to tackle climate change. From the result, we briefly argue that student’s climate should be integrated in school learning in a form of climate change education to ensuring them taking their climate action in daily life.